Differences in Gastric Mucosal Microbiota Profiling in Patients with Chronic Gastritis, Intestinal Metaplasia, and Gastric Cancer Using Pyrosequencing Methods. Issue 6 (23rd July 2014) - Eun, Chang Soo; Kim, Byung Kwon; Han, Dong Soo; Kim, Seon Young; Kim, Kyung Mo; Choi, Bo Youl; Song, Kyu Sang; Kim, Yong Sung; Kim, Jihyun F.
Abstract: Background: Helicobacter pylori ( H. pylori ) infection plays an important role in the early stage of cancer development. However, various bacteria that promote the synthesis of reactive oxygen and nitrogen species may be involved in the later stages. We aimed to determine the microbial composition of gastric mucosa from the patients with chronic gastritis, intestinal metaplasia, and gastric cancer using 454 GS FLX Titanium. Methods: Gastric mucosal biopsy samples were collected from 31 patients during endoscopy. After the extraction of genomic DNA, variable region V5 of the 16S rRNA gene was amplified. PCR products were sequenced using 454 high‐throughput sequencer. The composition, diversity, and richness of microbial communities were compared between three groups. Results: The composition of H. pylori ‐containing Epsilonproteobacteria class appeared to be the most prevalent, but the relative increase in the Bacilli class in the gastric cancer group was noticed, resulting in a significant difference compared with the chronic gastritis group. By analyzing the Helicobacter ‐dominant group at a family level, the relative abundance of Helicobacteraceae family was significantly lower in the gastric cancer group compared with chronic gastritis and intestinal metaplasia groups, while the relative abundance of Streptococcaceae family significantly increased. In a UPGMA clustering of Helicobacter ‐dominant group based on UniFrac distance, the chronic gastritis group and gastric cancer group were clearly separated, while the intestinal metaplasia group was distributed in between the two groups. The evenness and diversity of gastric microbiota in the gastric cancer group was increased compared with other groups. Conclusions: In Helicobacter predominant patients, the microbial compositions of gastric mucosa from gastric cancer patients are significantly different to chronic gastritis and intestinal metaplasia patients. These alterations of gastric microbial composition may play an important, as‐yet‐undetermined role in gastric carcinogenesis of Helicobacter predominant patients.